A Palaeoecological Investigation of the Treeline Zone North of Yellowknife, NWT - Moser, Katrina Ann (My University, 1988)
The pollen, charcoal and sediment stratigraphies of two cores from small lakes located northeast of Yellowknife, NWT are examined. The focus of this study is to reconstruct post-glacial vegetation changes in this climatically sensitive area. The resulting vegetation history is compared to similar reconstructions from across Canada. The pollen content of twenty-eight modern sediment samples, collected from the forest, the forest-tundra and the tundra zones were used to aid in the interpretation of the fossil record. Radiocarbon dates indicate that the fossil records from these lakes span ~7 500 years. The initial vegetation, shrub Betula tundra, was established at ~7 000 BP and persisted until ~6 000 BP. The presence of Ericaceae, Myrica, and Sphagnum distinguishes this zone from similar zones from western Canada and suggests the existance of large areas of bog environment. This zone is succeeded by a second shrub tundra zone, which is marked by a dramatic increase in Alnus crispa and Alnus incana. This zone spans from ~6 000 BP until ~5 000 BP. A synchronous increase in Alnus is noted from sites across Canada and is attributed to an increase in moisture. The third zone, spanning from ~5 000 BP to ~3 500 · BP, delimits the existance of forest vegetation defined by the northward expansion of Picea mariana. The delay of Picea mariana expansion into the area relative to its arrival in western Canada can be explained by one of the following: 1) geological differences; or 2) remnant glacial ice retarding climatic amelioration; or 3) the long-wave westerly disturbance, which causes cooler temperatures in the east when warmer temperatures persist in western Canada; or 4) some combination of the above. The decline of forest vegetation at ~3 500 BP marks the establishment of modern tundra vegetation at both sites. Climatic cooling coupled with fire caused the extinction of aboreal vegetation at the study sites.
Keywords: palaeoecological, investigation, Treeline, zone, Yellowknife, NWT, pollen, charcoal, sediment, forest vegetation, Picea mariana